Erosion Mapping Based on Erosion Evidence Features in the Micro Watershed of Parangtritis - Lathifah, Rofiatun Nur; Setiawan, Muhammad Anggri (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
This study involves detailed observations of erosion indicators within the watershed to produce a comprehensive mapping of erosion patterns. The detailed mapping of erosion patterns and spatial distribution, along with the factors influencing erosion, is essential. Mapping erosion spatially often yields data that may differ from the actual erosion conditions observed in the field, there is a need for a more accurate yet efficient mapping of erosion hazard levels by combining spatial analysis methods and field surveys. The primary focus of the research is to develop an efficient erosion mapping survey procedure at the Micro Watershed Scale, considering diverse erosion typologies and land-use dynamics. The Micro Watershed of Parangtritis, chosen for its unique erosion characteristics, was used as the main research area. This mapping method involves a combination of field surveys and geospatial analysis to capture various erosion features. Important data to collect are various erosion and landform features based on their geomorphology and anthropogenic features. The mapping results demonstrate complex erosion patterns. Topography, vegetation cover, anthropogenic, and soil types play key roles in erosion distribution. Steep slopes and insufficient ground cover vegetation significantly contribute to the soil erosion. In the upstream area of the watershed, characterized by steep topography and a predominantly natural anthropogenic, there is a tendency for severe erosion, including 8.87 ha (6.38%) classified as Very Severe, 16.81 ha (12.08%) as Severe, 23.46 ha (16.87%) as Catastrophic, and 11.81 ha (6%) as High. Meanwhile, in the downstream area with relatively flat topography and an urbanogenic and agrogenic, erosion tends to be light, with 23.34 ha (16.78%) classified as Light, 7.08 ha (5.09%) as Moderate, and 28.63 ha (30.98%) as Very Light. These findings reveal diverse evidence of erosion, including splash erosion, sheet erosion, rill erosion, gully erosion, and landslides, and influenced by variations of topography, vegetation cover, anthropogenic, and soil types that significantly contribute to the erosion patterns within the watershed. Special attention is given to micro-sized erosion features that may not be visible through broader mapping methods. This detailed mapping approach provides valuable insights into the spatial distribution of erosion, facilitating more targeted conservation efforts. These findings contribute to a deep understanding of erosion patterns in the karst environment and provide fundamental information for soil and water conservation planning. In the context of environmental sustainability, detailed-scale erosion mapping in the Micro Watershed Area needs to further explore the anthropogenic influences on erosion occurrence.